2015
DOI: 10.1177/0143831x15572836
|View full text |Cite
|
Sign up to set email alerts
|

Labour productivity and innovation performance: The importance of internal labour flexibility practices

Abstract: This article develops and examines the idea that internal labour flexibility practices are beneficial for labour productivity and innovation performance of companies. This is tested in two studies using unique company level datasets. In Study 1, results obtained from 377 independent companies revealed that internal labour flexibility practices are positively related to objective labour productivity and its growth in the year following, also when controlled for objective labour productivity and objective extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 97 publications
2
57
0
2
Order By: Relevance
“…Here, for instance, Chen et al (2014) found that HR management practices affect product innovation performance of the company. Preenen et al (2017) focus on internal labor flexibility and confirmed the relationship between internal labor flexibility and product innovation. A possible explanation could be an early study of Arvanitis (2005), who argues that product innovation requires highly-skilled technicians and scientists, while companies sometimes hire high-skilled personnel temporarily for certain tasks, from other institutions.…”
Section: Product Innovation As Outcomementioning
confidence: 60%
“…Here, for instance, Chen et al (2014) found that HR management practices affect product innovation performance of the company. Preenen et al (2017) focus on internal labor flexibility and confirmed the relationship between internal labor flexibility and product innovation. A possible explanation could be an early study of Arvanitis (2005), who argues that product innovation requires highly-skilled technicians and scientists, while companies sometimes hire high-skilled personnel temporarily for certain tasks, from other institutions.…”
Section: Product Innovation As Outcomementioning
confidence: 60%
“…The first principle is that job quality is constituted by a set of work features that have the capability of enhancing or diminishing worker well-being. Research evidence suggests that good jobs are also good for employers in that they are associated with increased productivity, lower absenteeism and longer job tenure (Preenen et al, 2017). For example, greater employee involvement in decision making has been shown to deliver bottom-line benefits to business (Appelbaum et al, 2000).…”
Section: Conceptions Of Job Qualitymentioning
confidence: 99%
“…Numerical flexibility can be enhanced through various practices, such as the use of fixed-term workers, temporary workers or agency workers. Since these practices require firms to interact with external labour markets, they are often referred to as "external numerical flexibility" (Kalleberg, 2001;Preenen et al, 2017). However, firms can also adjust the volume of labour through flexible working hour arrangements for existing workers, such as voluntary part-time work, overtime and weekend and shift work.…”
Section: A Labour Flexibility Productivity and Employment Outcomesmentioning
confidence: 99%